Hubungan Insomnnia Dengan Motivasi Belajar pada Mahasiswa Sekolah Tinggi Ilmu Kesehatan Guna Bangsa Yogyakarta - Eni Purwaningsih (LPPM STIKES Guna Bangsa Yogyakarta, 2014)
Background: Insomnia is difficulty starting and maintaining sleep which is one of the most common sleep disorders experienced by students. Lack of sleep can disrupt the learning motivation, innovative thought processes, flexible decision-making process and some other cognitive functioning, we know that students must have a strong motivation to learn as well as critical and innovative in the lesson and complete the task during the lecture. The initial data results of interviews with 60 students Guna Bangsa School Of Health Sciences Yogyakarta had obtained 32 students insomnia in last for 1 month. From 32 students who experience insomnia, 25 students said that during the day feel sleepy and tired easily and become lazy to learning.